Identifying weight management clusters and examining differences in eating behaviour and psychological traits: An exploratory study. (1st August 2022) - Gatzemeier, Jennifer; Wilkinson, Laura L.; Price, Menna; Lee, Michelle D.
Abstract: Previous research has suggested differences in psychological traits and eating behaviours between groups of individuals with varying weight management profiles, for example, differences between individuals who have maintained weight loss compared to those who have not. However, no study has looked at differences in traits across a sample with a broad range of characteristics including variations in bodyweight and its management. Across two studies, we identified and validated weight management profiles using a clustering approach and examined trait differences across groups. Data were collected using online questionnaires (Study 1: secondary data analysis; Study 2: primary data analysis allowing for cluster validation). Cluster analysis was implemented with BMI, diet history, weight suppression (difference between highest and current weight) as primary grouping variables, and age and gender as covariates. Differences in psychological and eating behaviour traits (e.g., restraint) were explored across clusters. In study 1, 423 participants (27.21 ± 9.90 years) were grouped into 5 clusters: 'lean men', 'lean young women', 'lean middle-aged women', 'successful' and 'unsuccessful dieters'. The cluster structure was broadly replicated with two additional groups identified ('lean women without dieting' and 'very successful dieters') in study 2 with 368 participants (34.41 ± 13.63 years). In both studies, unsuccessful dieters had higher restrained and emotional eating scores than lean individuals, and in study 1, they also had higher food addiction scores than successful dieters. Individuals could be grouped in terms of their weight management profiles and differences in psychological and eating behaviour traits were evident across these groups. Considering the differences in traits between the clusters may further improve the effectiveness and adherence of weight management advice.